Frontonasal Fold Thickness–to–Nasal Bone Length Ratio as a Prenatal Sonographic Marker for Trisomy 21 in a Low‐Risk Population. (1st May 2013) - Gonzalez, Ruben; Aedo, Socrates; Dezerega, Victor; Sepulveda, Waldo
Abstract : Objectives: To report normative data for the fetal nasal bone length (NBL), frontonasal fold (FNF) thickness, and the FNF/NBL ratio and to study their performance in the sonographic screening of trisomy 21 in a normal, unselected Latin American population. Methods: Women undergoing a routine sonographic examination between 16 and 32 weeks' gestation at a primary health care center in Santiago, Chile, were prospectively recruited for NBL and FNF thickness measurements. Pregnancies with maternal/fetal complications were subsequently excluded from analysis. Correlations between NBL, FNF thickness, and FNF/NBL ratio and gestational age were assessed with the Spearman correlation coefficient (ρ). To generate reference percentiles for NBL and FNF thickness, adjusted regression models were derived using a statistical method for calculating reference percentiles of fetal biometric parameters. Results: A total of 1922 cases complied with entry criteria. Both the NBL and the FNF thickness increased with gestational age. However, the FNF/NBL ratio remained constant (ρ= 0.016; P = .95), with a mean value of 0.68 and 95th and 99th percentile values of 0.84 and 0.90, respectively. During the study period, all 4 fetuses with trisomy 21 diagnosed in this low‐risk population had an FNF/NBL ratio above the 99th percentile, whereas only 3 had NBL below the fifth percentile, and 3 had FNF thickness above the 95th percentile. Conclusions: The FNF/NBL ratio is a promising marker for the sonographic screening of trisomy 21 in the low‐risk population; however, further prospective studies including larger numbers of fetuses with trisomy 21 are warranted to determine the clinical value of this marker. As the NBL is dependent on the ethnicity of the population screened, determination of normative data for NBL and the FNF/NBL ratio in different ethnic populations is also recommended before including this method in the routine screening for aneuploidy.